Three-year survival of ART and conventional restorations in patients with disability - Molina, Gustavo Fabián (2016)
Fil: Molina, Gustavo Fabián. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Materiales Dentales; Argentina.